Unilateral Acute Anterior Ischemic Optic Neuropathy in a Patient with an Already Established Diagnosis of Bilateral Optic Disc Drusen - Ziya Ayhan; Aylin Yaman; Meltem Söylev Bajin; A. Osman Saatci (Case Reports in Ophthalmological Medicine)
Optic disc drusen (ODD) are calcific deposits that form in the optic nerve head secondary to abnormalities in axonal metabolism and degeneration. Anterior ischemic optic neuropathy, central retinal artery, and vein occlusion are among the rare vascular complications of disc drusen. We reported the clinical course of a 51-year-old patient with a unilateral acute nonarteritic anterior ischemic optic neuropathy (NAION) who received the diagnosis of bilateral optic disc drusen five years earlier and thereby reiterated the association of ODD and acute NAION.